Behcet’s Disease Presenting with Focal Fibrosing Mediastinitis and SVC Thrombosis: A Case Report with Review of Literature - Soran H. Tahira; Fahmi H. Kakamad; Dlsoz M. Hussein; Shorsh A. Mohammed; Rezheen J. Rshid; Karzan M. Salih; Shvan H. Mohammed; Hussein M. Hamasalih; Abdulwahid M. Salih (Barw Medical Journal, 2023)
AbstractIntroductionBehcet's disease is a rare, multisystemic disease marked by vasculitis and a triad of recurrent oral and genital mucosa ulcers, as well as relapsing uveitis and thrombophlebitis. Mediastinal fibrosis is extremely rare in Behcet's disease.Case presentationWe present ultrasound and computed tomography (CT scan) in a 26-year male with mediastinal fibrosis and superior vena cava (SVC) thrombosis, with thrombus in left internal jugular veins (IJV) associated with Behcet’s disease.ConclusionBehcet's disease can cause mediastinal fibrosis in rare cases. CT and MRI are efficient methods for detecting mediastinal fibrosis and superior vena cava thrombosis.